Religious Politics in Latin America, Pentecostal vs. Catholic - Smith, Brian H., 1940- (Book collections on Project MUSE., 1998)
Significant religious and cultural transformations are underway throughout Latin America which will alter the contours of society. Brian H. Smith sheds light on these changes with a survey of the recent trends in Pentecostal and Catholic religion and politics in this region.